In-sacco nutritional worth and in-vitro methane production potential of leguminous forages - LAMBA, J S; WADHWA, M; KAUR, K; BAKSHI, M P S (The Indian Journal of Animal Sciences, 2013)
The present study was undertaken to assess the in-vitro methane production potential of multi-cut berseem, lucerne and shaftal at different cuts. The CP and EE content declined, while the cell wall constituents increased linearly with the increase in number of cuts. The in-sacco studies revealed that the degradation rate and effective degradability (ED) of DM was highest (P<0.01), while the rumen un-degradable fraction (UDF) and rumen fill values were the lowest in shaftal. The degradation rate and ED of DM declined, while the UDF and rumen fill values increased with the increase in number of cuts. The digestion kinetic parameter of CP revealed that the UDP as per cent of CP was higher in berseem followed by that in shaftal. The ED and UDP as per cent of CP declined linearly with the increase in number of cuts. The digestion kinetic parameter of NDF revealed that shaftal had the highest ED and lowest UDF, while reverse trend was observed in berseem. The rumen fill values also confirmed that shaftal had better palatability than that of lucerne and berseem. The ED declined, while the UDF and rumen fill values increased with the increase in number of cuts. The in vitro gas production analysis revealed that irrespective of cuts, the tested leguminous forages produced almost same amount of gas even though the digestibility of NDF and OM of berseem was lower than that of lucerne and shaftal. The methane production at t1/2 (expressed as ml/g digestible OM) was lowest in shaftal as compared to berseem and lucerne. The digestibility of NDF and OM was lowest in the fourth cut fodders. Accordingly, the methane production at tÂ½ increased linearly with the number of cuts and was highest in the fourth cut fodders. Irrespective of cuts, total VFAs production varied from 6.6 mM/dl in shaftal to 7.95 mM/dl in lucerne. Lucerne produced highest amount of acetate, propionate and butyrate, followed by that produced by berseem. Irrespective of fodder species, the relative proportion of propionate declined with the number of cuts. It was concluded that amongst the tested multi-cut leguminous forages, the use of shaftal in the diet of ruminants may help in mitigating enteric methane production and that the enteric methane production increased with the number of cuts of the forage.